The Historical Comparison and Research Significance of “Difficult Situation” System and “Change of Situation” System—Take COVID-19 as the Research Background - Yilin Liu (Law and Economy, 2022)
At the beginning of 2020, the global outbreak of COVID-19 led to huge setbacks in the economic and social development of various countries, resulting in the fact that many international and domestic commercial contracts were unable to perform or perform with too high costs.”Difficult situation” and “situation change” are respectively the concept of PICC and Chinese law, this paper is a comparative study of the two, aiming to provide some references for Chinese enterprises when they are considering the term of situation change in commercial contracts, improve their risk-prevention awareness and dispute-resolution ability,as well as partially resolve the current contract performance disputes affected by COVID-19 outbreak , and provide ideas to prevent similar events in the future.